Assessment of Formality, Innovation and Productivity in Small and Medium Enterprises of Pakistan - Sadaf, Mamona; Hassan, Nadia; Latif, Muhammad Ijaz (South Asian Review of Business and Administrative Studies (SABAS), 2023)
This study aims to assess the dynamics of innovation and productivity of formally registered small and medium enterprises in Pakistan. It considers learning by doing and learning by schooling theories along with stylized facts about determinants of firms’ ability to practice innovation. This is the first detailed study that considers learning by doing and learning by schooling aspects of firms determining innovation practices. These are considered building blocks of sustainable economic growth and hence the growth processes of the firms. Realizing the state of these aspects provides valuable support to policymakers in developing effective policies for the manufacturing sector. For this purpose, a structural model is used to assess the factors affecting innovation followed by the effects of innovation on the productivity of the firms with reference to formality. The latest data by World Bank collected through Enterprise Survey between May 2013 to May 2015 is used to address the purpose. It is found that novel organizational and management practices promote the innovation of small and medium firms significantly. It is concluded that higher levels of productivity can be achieved through better organizational structure, employee training, the transformation of the internal structure of the production process, export growth, and the development of the business environment in various locations. These findings imply that export-oriented policies, research, and development for SMEs, training provisions for managers and employees, and changes in the hierarchal structure of the old established enterprises are the key elements for SMEs growth in Pakistan. Therefore, it is suggested to promote positive competition among SMEs as it works as a driving force to bring innovation and enhance the capacity utilization of the firms. It is observed that non-exporting firms are less concerned to adopt innovative practices that limit their productivity and growth. Thus, it is recommended to encourage these firms to grow at the par of their exporting counterparts by following their innovative strategies. These strategies bring direct benefits to the firms in terms of productivity and growth and have the potential to ultimately improve the livelihood and socio-economic status of the associated employees. Moreover, with higher levels of growth informal sector may also catch up with the formal sector through the effect of agglomeration economies of the formal firms located in the region.